Hepatitis B notifications in a vaccinated cohort of Aboriginal people in the Kimberley region. Issue 6 (15th September 2014) - Griffiths, Emma; Reeve, Carole; Marley, Julia V
Abstract: Objectives: To identify cases of hepatitis B infection after vaccination in Kimberley residents and determine maternal serostatus as a potential indicator of mode of transmission. Design and participants: Retrospective review of Kimberley residents with notified hepatitis B infection using records of vaccination history and child and maternal serology. Main outcome measures: Confirmed cases of hepatitis B infection after vaccination; chronic infection in cases of hepatitis B infection after vaccination; maternal serostatus in confirmed cases of hepatitis B infection after vaccination. Results: From 1 January 1984 to 31 March 2011, we identified 17 cases of Aboriginal residents with hepatitis B infection after vaccination (10 chronic infections, five not defined and two cleared). In six patients, maternal chronic infection had been identified at some stage, raising the possibility of vertical transmission. In seven patients, maternal serology or evidence of subsequent acquisition suggested that horizontal transmission and therefore vaccination failure was likely. For four patients, there was inadequate information to assess possible mode of transmission. Conclusions: Hepatitis B infection after full vaccination is not limited to children of mothers with active infection. Further undiagnosed infections in the Kimberley are likely, and active monitoring to detect the extent and likely cause of hepatitis B infection in vaccinated children is needed. In children where vertical transmission is a risk, prospective follow‐up is warranted.